Analysis of Levator Function and Ptosis Severity in Involutional Blepharoptosis. (March 2017) - Lai, Hsin-Ti; Weng, Shih-Feng; Chang, Chih-Hau; Huang, Shu-Hung; Lee, Su-Shin; Chang, Kao-Ping; Lai, Chung-Sheng
Abstract : Background: Involutional blepharoptosis is the most common type of acquired blepharoptosis. The etiology is believed to be the degeneration of the levator aponeurosis, and levator superioris muscle function was believed to be normal. However, there are a few studies analyzing levator function (LF) in involutional blepharoptosis. Our study aimed to access the LF abnormality in involutional blepharoptosis and analyze the correlation between LF and ptosis severity in involutional blepharoptosis in Taiwan. Methods: We reviewed the medical records of patients who underwent ptosis correction surgery between October 2011 and December 2015 after receiving a diagnosis of involutional blepharoptosis. This study examined patient sex and age, preoperative LF, margin reflex distance of the upper eyelid (MRD1), and ptosis severity. Linear regression was performed for statistical analysis. Levator muscle specimen was sent for pathologic examination. Results: We analyzed 231 eyelids of 126 patients. Average MRD1 was 0.43 ± 2.15 mm. Average LF was 14.30 ± 2.51 mm. Overall, 77.1% (178/231) of involutional blepharoptotic eyelids had normal LF (more than 12 mm). Forty-three (18.6%) of 231 were good (10–12 mm), and 10 (4.3%) of 231 were fair (6–9 mm). No patients with poor levator function (⩽5 mm) were observed in our case series. A positive correlation between LF and MRD1 was observed after statistical analysis. On average, a 0.6-mm reduction in LF was observed for each 1.0-mm decrease in MRD1. Fat infiltration in levator muscle is observed both grossly and microscopically in most cases with varied degrees. Conclusions: Levator function and MRD1 were positively correlated in patients with involutional blepharoptosis. In our study, 77.1% (178/231) of eyelids had normal levator function, which meant there was 23.0% (53/231) of eyelids had abnormal LF, in contrast to current literature. Fat infiltration was common in our series. In Asian involutional blepharoptosis, LF was not always excellent and it had positive correlation with ptosis severity.